Analysis of Figurative Language Used in Selected Song Lyrics by Niki Zefanya - Putra, Aidil Syah; Dalpah, Dalpah; Cintya, Novi (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
This study analyzes of the figurative language used in the song lyrics by Niki Zefanya. This research aims to find out the figurative language used in the lyrics of the song lyrics. This method uses qualitative data to find out the figurative language contained used in selected the lyrics songs entitled "Autumn", and "Lowkey" "Too many good things" by Niki Zefanya which have been released and received many viewers. Data collection uses observation techniques using the theory (Abrams, 2018) to categorize figurative language. The results of this study found 9 data from 10 types of figurative language displayed. In the selected lyrics of the song by Niki Zefanya, there are types of figurative language, such as metaphor, simile, hyperbole, personification, synecdoche, allusion, symbolism, metonymy, and irony. The researcher concluded that the most common figurative languages found used in selected the lyrics of the song by Niki Zefanya are hyperbole.